Global, regional, and national burden of ischemic heart disease attributable to lead exposure, 1990–2021: decomposition, frontier, and projection analysis - Wen, Xinyue; Qiao, Lichun; Deng, Feidan; Zhou, Jingxuan; Li, Miaoqian; Wang, Lin; Deng, Huan; Amhare, Abebe Feyissa; Han, Jing; Guo, Yijie (Frontiers in Public Health, 2025)
IntroductionIschemic heart disease (IHD) is a leading global health burden, with lead exposure identified as a significant environment risk factor contributing to its prevalence.MethodsData from the Global Burden of Disease Study (GBD) 2021 were used to analyze deaths and disability-adjusted life years (DALYs) of IHD due to lead exposure at global, regional, and national levels. Decomposition analysis, frontier analysis, and Bayesian age-period cohort (BAPC) models were applied to assess trends from 1990 to 2021.ResultsIn 2021, deaths and DALYs attributable to lead exposure reached 590,370.03 and 11,854,611.43, respectively, though age-standardized rates (ASRs) declined. Males and the older adult exhibited higher ASRs. At regional level, South Asia had the highest number of deaths and DALYs, while North Africa and the Middle East had the highest ASRs. Certain countries showed increasing ASRs over time, with a negative correlation between socio-demographic index (SDI) and ASRs. Decomposition analysis identified that population growth as the primary driver of increasing deaths and DALYs, particularly in middle-SDI regions. Frontier analysis suggested that middle and low-SDI regions have the greater potential to reduce the IHD burden. BAPC projections indicated a global decrease in IHD burden due to lead exposure by 2050.ConclusionsThe burden remains disproportionately high in males, the older adult and low- and middle-SDI regions, highlighting the need for targeted prevention and lead exposure control efforts in these populations.